Integrated age‐related immunohistological changes occur in human olfactory epithelium and olfactory bulb. Issue 12 (9th April 2022) - Fitzek, Mira; Patel, Parthkumar K.; Solomon, Peter D.; Lin, Brian; Hummel, Thomas; Schwob, James E.; Holbrook, Eric H.
Abstract: Olfactory epithelium (OE) is capable of lifelong regeneration due to presence of basal progenitor cells that respond to injury or neuronal loss with increased activity. However, this capability diminishes with advancing age and a decrease in odor perception in older individuals is well established. To characterize changes associated with age in the peripheral olfactory system, an in‐depth analysis of the OE and its neuronal projections onto the olfactory bulb (OB) as a function of age was performed. Human olfactory tissue autopsy samples from 36 subjects with an average age of 74.1 years were analyzed. Established cell type‐specific antibodies were used to identify OE component cells in whole mucosal sheets and epithelial sections as well as glomeruli and periglomerular structures in OB sections. With age, a reduction in OE area occurs across the mucosa progressing in a posterior‐dorsal direction. Deterioration of the olfactory system is accompanied with diminution of neuron‐containing OE, mature olfactory sensory neurons (OSNs) and OB innervation. On an individual level, the neuronal density within the epithelium appears to predict synapse density within the OB. The innervation of the OB is uneven with higher density at the ventral half that decreases with age as opposed to stable innervation at the dorsal half. Respiratory metaplasia, submucosal cysts, and neuromata, were commonly identified in aged OE. The finding of respiratory metaplasia and aneuronal epithelium with reduction in global basal cells suggests a progression of stem cell quiescence as an underlying pathophysiology of age‐related smell loss in humans. Key points: A gradual loss of olfactory sensory neurons with age in human olfactory epithelium is also reflected in a reduction in glomeruli within the olfactory bulb. This gradual loss of neurons and synaptic connections with age occurs in a specific, spatially inhomogeneous manner. Decreasing mitotically active olfactory epithelium basal cells may contribute to age‐related neuronal decline and smell loss in humans. Abstract : During human development a complete uninterrupted sheet of neuronal competent mucosa with well demarcated borders comprises the olfactory epithelium (OE) within the superior aspect of the nasal cavity along the septum and lateral wall. The axons of olfactory neurons within the epithelium target glomeruli along the peripheral edges of the olfactory bulb (OB). With advancing age, regions of the OE are disrupted and replaced with respiratory or aneuronal epithelium while the border becomes less defined. A decreasing area of OE occurs with a shift of neuronal density in a more posterior‐dorsal direction. Intraepithelial neuromas and subepithelial cysts develop along with a decrease in olfactory sensory neurons (OSNs). Proximally, distortions in olfactory targeting occur within the OB with an overall reduction in synapses in the ventral portion.